Herbal medicine for acute rhinosinusitis in children - N.M. Tokareva; O.O. Ahafonova; L.L. Petrenko (Zaslavsky O.Yu., 2021)
Rinosinusitis is a common disease in most countries of the world, which determines significant economic costs caused by the consumption of medical services and a decrease in a labor productivity. The annual prevalence of acute rhinosinusitis (ARS) is 6-15 %. ARS, as a rule, is a consequence of viral rhinorrhea and is usually self-limited, but serious complications leading to life threatening situations and even death were described. Taking into account the fact that doctors of different specialties, including pediatricians, general practitioners and otolaryngologists are faced with ARS, making the clear algorithm of action and prescribing the relevant pathogenetic therapy is an important problem of health care. In February 2020, the European Rhinologic Society published updated treatment guidelines for acute and chronic rhinosinusitis, as well as nasal polyps (European Position Paper on Rhinоsinusitis and Nasal polyps - EPOS-2020) in patients of different categories: children, adults, patients with concomitant diseases. The EPOS-2020 gives the clear definition of rhinosinusitis and diagnostic criteria for acute and chronic rhinosinusitis (CRS), a new integrated approach to providing medical care in ARS. ARS in children is diagnosed based on a typical clinical picture - a sharp beginning of typical symptoms: nasal congestion, colorless/light discharge from the nose and coughing within < 12 weeks. According to modern criteria, ARS includes three nosological units: acute viral (AVRS), post-virus (PVRS), and bacterial rhinositis (BRS). Treatment of patients with ARS should be comprehensive and should include elimination of inflammation, restoration of natural paranasal sinuses, evacuation of discharge from them, eradication of the pathogen, preventing the development of complications, local immunomodulatory therapy. The main groups of medicines used for the treatment of ARS include antibacterial, anti-inflammatory, mucolytic drugs. EPOS-2020 gives the leading place to the prescribing phytotherapy and provides data on specific herbal agents that have proven efficacy for the treatment of ARS: with AVRS - eucalyptic oil and Andrographis paniculata SHA-10; with PVRS - Pelargonium sidoides and myrtol. The main criterion for choosing therapy is the minimization of medicinal load with sufficient treatment effectiveness. This is the drug Respero Mirthol, which combines the mucokinetic, mucolytic, antimicrobial and anti-inflammatory properties. The main active ingredient is myrtol standardized, anti-inflammatory and sanogenetic effect of which has been proved in more than 100 preclinical and randomized clinical studies.